The folly of realism : how the West deceived itself about Russia and betrayed Ukraine - Vindman, Alexander S. (PublicAffairs, 2025)
"A bestselling national security expert delivers a chilling analysis of how Western indecision and apathy made possible the return of brutal Russian expansionism - with catastrophic consequences. After the collapse of the Soviet Union, U.S. presidential administrations of both parties pursued policies for Russia, Ukraine, and Eurasia that boosted Putin's Russia and made U.S. relations with all-important Ukraine secondary to the Russia relationship, thus unwittingly playing into Russia's imperialist, centuries-long myth of its supposed regional hegemony. The result should have been foreseeable: Russia's 2014 invasion of Crimea and 2022 invasion of Ukraine. As leading national-security expert and bestselling author Alexander Vindman argues, this history of U.S. missteps is bound up in policymakers' fixation on immediate, short-term, and transactional thinking. He proposes instead a long-term, values-based approach, where forthright insistence on the fundamentals of liberal democracy and a rules-based world order build positive partnerships while refusing to submit to the emotional blackmail of authoritarians. Enlivened by behind-the scenes interviews with big-name Washington policymakers in four administrations and climaxing in the shocking brutality of Putin's invasion of Ukraine, the book exposes the sources of a dangerously stubborn problem and shows the way to a better world"--